How Does Stochastic Ryanodine Receptor-Mediated Ca Leak Fail to Initiate a Ca Spark? - Sato, Daisuke (The Biophysical Society, 2011)
Spontaneous calcium (Ca) sparks are initiated by single ryanodine receptor (RyR) opening. Once one RyR channel opens, it elevates local [Ca] in the cleft space ([Ca](Cleft)), which opens other RyR channels in the same Ca release unit (CaRU) via Ca-induced Ca-release. Experiments by Zima et al. (J. Physiol. 588:4743–4757, 2010) demonstrate that spontaneous Ca sparks occur only when intrasarcoplasmic-reticulum (SR) [Ca] ([Ca](SR)) is above a threshold level, but that RyR-mediated SR Ca leak exists without Ca sparks well below this threshold [Ca](SR). We examine here how single RyR opening at lower [Ca](SR) can fail to recruit Ca sparks at a CaRU, while still contributing to SR Ca leak. We assess this using a physiologically detailed mathematical model of junctional SR Ca release in which RyR gating is regulated by [Ca](SR) and [Ca](Cleft). We find that several factors contribute to the failure of Ca sparks as [Ca](SR) declines: 1), lower [Ca](SR) reduces driving force and thus limits local [Ca](Cleft) achieved and the rate of rise during RyR opening; 2), low [Ca](SR) limits RyR open time (τ(O)), which further reduces local [Ca](Cleft) attained; 3), low τ(O) and fast [Ca](Cleft) dissipation after RyR closure shorten the opportunity for neighboring RyR activation; 4), at low [Ca](SR), the RyR exhibits reduced [Ca](Cleft) sensitivity. We conclude that all of these factors conspire to reduce the probability of Ca sparks as [Ca](SR) declines, despite continued RyR-mediated Ca leak. In addition, these same factors explain the much lower efficacy of L-type Ca channel opening to trigger local SR Ca release at low [Ca](SR) during excitation-contraction coupling. Conversely, all of these factors are fundamentally important for increasing the propensity for pro-arrhythmic Ca sparks and waves in cardiac myocytes at high [Ca](SR).